PROFESSIONAL EDUCATION IN SWITZERLAND: APPROACHES TO DEVELOPMENT OF CONTENT AND LEARNING OUTCOMES EVALUATION - Anton P. Romaev; Alla A. Lyamina (Вестник Северо-Кавказского федерального университета)
The item offers a view on the experience of Switzerland joining the Bologna process; there is also description regarding certain approaches to developing the content for professional training and ways to evaluate the learning outcomes.